PAPARAN IKLIM KERJA PANAS TERHADAP KEJADIAN HEAT STRAIN PADA PEKERJA DI PROYEK PEMBANGUNAN APARTEMEN THE PARC SOUTHCITY, PONDOK CABE, TANGERANG SELATAN TAHUN 2022 - Milenda Kurnia Ramadhanty, (2022)
Extreme environmental temperature such as hot working climate is one of the physical environmental factors. Hot conditions will affect the level of comfort felt by workers, the emergence of fatigue and other subjective complaints. Results Based on a preliminary study conducted with environmental temperatures in the three areas around 30.7˚C-32.6˚C and it was found that some workers complained of dizziness, fatigue, itching, skin, and muscle cramps while working in a hot working environment. Therefore, the researchers conducted a study of the factors associated with the incidence of heat strain in the workers of The Parc Southcity apartment construction project. The research method used is quantitative research with cross sectional design and the sample used is 92 respondents. The results showed that there was a relationship between hot working climate (p = 0.001) and the incidence of heat strain experienced by workers, while age (p = 0.396), nutritional status (p = 0.491), drinking water consumption (p = 445), workload ( p = 1,000), and years of service (p = 0.795) were not associated with the incidence of heat strain experienced by workers. The conclusion of this study is that there is a relationship between a hot working climate and the incidence of heat strain experienced by workers in the apartment construction project The Parc Southcity, Pondok Cabe, South Tangerang. Suggestions that can be given are increasing workers' rest time for work activities, providing resting places with cooler temperatures, providing information about the work climate to workers.